Pengaruh Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Hasil Belajar Siswa Pada Materi Bangun Ruang Di Kelas V SD Negeri Garot Aceh Besar - saraniza saraniza; Alfiati Syafrina; monawati Monawati (Universitas Syiah Kuala, 2022)
The study aims to determine the effect of the application of the Snowball Throwing learning model on student learning outcomes in building materials in Class V SD Negeri Garot Kec. Darul Imarah Kab. Aceh Besar. The approach used in this research is a quantitative approach. The type of research used is experimental with the design used being One group pretest-posttest. In this study, the population will be all fifth graders in SD Negeri Garot, Kec. Darul Imarah Kab. Aceh Besar while the sample in this study is all students of class Va, the number of students in class Va is 30. The study was carried out for 4 days. The data collection technique was carried out by giving pre-test questions and also post-test questions. The data analysis technique used the average value of the pre-test and also the post-test, and also the hypothesis testing using the t-test statistic. The results showed that count = 6.628 while table = 1.70 so it can be seen that if count table, it is 6.628 1.70. Thus H0 is rejected and H1 is accepted, so the hypothesis in this study states that